ANALISIS YURIDIS TANGGUNG JAWAB NOTARIS DALAM MEMBUAT DAN MENYIMPAN MINUTA AKTA - MAYA MALINDA PANJAITAN (PREMISE LAW JURNAL, 2017)
A Notary as a public official who has the authority to make authentic deed, in doing his job, is bound to his obligation he has to comply with; he has to keep the deed minutes as part of the Notarial protocol. He has to keep them because they constitute the State’s archives/documents which have to be cared and kept in a safe place to prevent them from damaged or getting lost. If they are lost, the Notary is considered committing an offense, and a sanction will be imposed on him by the Regional Supervisory Council according to whether the offense is a serious violation or only a minor offense. The result of the research shows that after the deed minutes are made, they have to be kept is a safe place so that they will not be damaged or lost. The Notary has to write other minutes and report them to the Regional Supervisory Council so that the Local or Regional Supervisory Council can give the solution of how to settle the damaged or lost minutes. It is recommended that the Notarial Act be reviewed by enacting clear regulation concerning damaged or lost minutes, and a Notary should be very careful in keeping deed minutes.Keywords: Deed Minutes, Damaged or Lost